A Review on Models for Evaluating Rock Petrophysical Properties - A. Mahdi, Zahraa; Farman, Ghanim M. (Iraqi Journal of Chemical and Petroleum Engineering, 2023)
The evaluation of subsurface formations as applied to oil well drilling started around 50 years ago. Generally, the curent review articule includes all methods for coring, logging, testing, and sampling. Also the methods for deciphering logs and laboratory tests that are relevant to assessing formations beneath the surface, including a look at the fluids they contain are discussed. Casing is occasionally set in order to more precisely evaluate the formations; as a result, this procedure is also taken into account while evaluating the formations. The petrophysics of reservoir rocks is the branch of science interested in studying chemical and physical properties of permeable media and the components of reservoir rocks which are associated with the pore and fluid distribution. Throughout recent years, several studies have been conducted on rock properties, such as porosity, permeability, capillary pressure, hydrocarbon saturation, fluid properties, electrical resistivity, self-or natural-potential, and radioactivity of different types of rocks. These properties and their relationships are used to evaluate the presence or absence of commercial quantities of hydrocarbons in formations penetrated by, or lying near, the wellbore. A principal purpose of this paper is to review the history of development the most common techniques used to calculate petrophysics properties in the laboratory and field based primarily on the researchers and scientists own experience in this field.